Evapotranspiration-Based Irrigation for Agriculture: Crop Coefficients of Some Commercial Crops in Florida - Isaya Kisekka; Kati W. Migliaccio; Michael D. Dukes; Jonathan H. Crane; Bruce Schaffer; Sandra M. Guzman; Haimanote K. Bayabil (EDIS)
Part of a series on ET-based irrigation scheduling for agriculture, this article identifies typical Kc values for some of the crops commonly grown in Florida. Originally published January 2010 with minor update February 2013. This revision with Sandra M. Guzman, and Haimanote K. Bayabil